Social objectives of palliative day care groups - Payne, Malcolm; Hartley, Nigel; Heal, Rosanna (Groupwork, 2012)
This paper reports an evaluation by patients, staff and volunteers involved in different types of groupwork in a palliative day care centre; policy comment and research suggests that social as opposed to healthcare objectives in palliative day care are ill-defined. Staff and volunteers completed questionnaires (n=48) and patients were interviewed (n=37) about nine social objectives formulated from the palliative day care and groupwork literature. The results demonstrate agreement between patients, staff and volunteers about objectives, with most objectives assessed being positively identified as being helpful. Formal activity groups organised around creative arts, involving creation of an artistic object were more important to staff and volunteers, while patients gave equal importance to less formal social groups. Staff valued patients supporting each other about their illness and death, while patients were divided, with some preferring not to share. The researchers suggest that the staff and volunteers’ focus on creative activities and outcomes led them to give less priority to specific efforts to engage patients in social skill development to combat social isolation.